Knowledge, Attitude and Practices of Fruit Consumption among Female and Male Adolescents in Hulu Terengganu and Marang, Malaysia - Jamaludin, Nurul Atikah; Khalili Rohin, Mohd Adzim; Abd Hadi, Norhayati Binti (Jurnal Gizi dan Pangan, 2022)
The study aimed to determine the level of knowledge, attitude and practice of fruit consumption and their associations among female and male adolescents in Hulu Terengganu and Marang. This a crosssectional study involving 184 selected secondary school students in Hulu Terengganu and Marang, with 94 of them were female respondents and 90 were male. Data on socio-demographic, fruit consumption, knowledge, attitude and practices of fruit consumption were collected using validated questionnaire and food frequency questionnaire. Only 35.8 % of the respondents had adequate fruit consumption, 62.8% and 60.0% of female and male respondents had good knowledge, 63.8% and 60.0% of female and male respondents had good attitude and only 6.4% and 16.7% of female and male respondents had good practice. We also found a significant difference of practice in fruit consumption between male and female respondents (p<0.05). The result showed that there was positive significant correlations between knowledge and attitude as well as attitude and practices of fruit consumption (p<0.05). No correlation was reported between knowledge and practices of fruit intake. This showed that good attitude potentially improved knowledge and practice towards fruit consumption and vice versa. The results of this research showed that it is crucial to improve the main factors to influencie knowledge, attitude and practices of fruit consumption among adolescents.